A study on using corrective feedbacks in teaching essays at school of foreign languages, Thai Nguyen university - Le Thi, Nhung; La Thi, Thuy Dung (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2020)
The ability of writing is considered as a main communication skill and “a unique asset” in SLA (Chastain, 1998) that language learners should be fully aware of. Methodology in teaching writing therefore has experienced considerable changes in the approach to teaching and assessing learners. Written corrective feedback as a response channel to students’ writings in SLA classrooms has been a topic of inclusive debates and inquiries amongst the scholarly sphere. Contributing to this bulk of controversy, the present study investigates teachers’ perceptions and their students’ attitudes and evaluations as to the practice of error corrective feedback. To collect data, two different questionnaires of suitable reliability were delivered to sample respondents of 12 teachers and 34 students respectively to elicit data catering the study’s purposes. Findings were also triangulated with 5 participant teachers invited for follow up interviews and a comparative reference to previous studies on written corrective feedbacks. The results revealed that there are no dramatic differences in teachers’ attitudes towards the usefulness of written corrective feedbacks. However, when it comes to types and amount of errors they should comment on, teachers’ responses and preference cover a wide spectrum.